The pragmatic functions of metonomy in cross-linguistic perspective: evidence from English and Uzbek - Bozorova , Dilafza Ikrom qizi (The Lingua Spectrum, 2026)
Metonymy functions as a key pragmatic device enabling indirectness, emotional expression, and referential economy in everyday discourse. Although previous research has explored metonymy in English and Uzbek from stylistic and cognitive angles, systematic cross-linguistic studies on its pragmatic functions remain scarce. This study aimed to examine the pragmatic functions of metonymy in English and Uzbek, highlighting both universal mechanisms and culture-specific patterns. Using a mixed-methods design, the research combined qualitative discourse analysis with quantitative corpus techniques on a comparable one-million-word corpus of news, opinion, literary, and spoken texts from both languages. Results showed that referential economy was the dominant function in both languages, while Uzbek exhibited significantly higher use of metonymy for emotional intensification and politeness, whereas English favored indirect evaluation. Chi-square analysis confirmed statistically significant cross-linguistic differences. The findings demonstrate that pragmatic exploitation of metonymy is shaped by cultural norms and national identity. This study contributes to cross-linguistic pragmatics and offers implications for translation and language teaching.